PENGEMBANGAN KUIS INTERAKTIF DENGAN CLASSPOINT BERBASIS KURIKULUM MERDEKA PADA MATA PELAJARAN EKONOMI - Rahayu, Riska; Andayani , Endah; Mardiana, Riril (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2024)
The aim of this research is to determine the process of developing interactive quizzes with classpoints based on the independent curriculum in class X economics subjects at SMA Negeri 6 Malang and to analyze their feasibility. Research using the ADDIE model research and development (R&D) approach with 5 stages is the focus of the research, namely; (1) analysis, (2) design, (3) development, (4) Implementation (5) Evaluation. The results of the feasibility validation from the three validators are as follows; (1) material expert validation obtained 92.5% with a very feasible category with the advantage of being able to change the material and add material for example market structure material, (2) media expert validation obtained 95% with a very feasible category with the advantage of classpoint which has many features so that it can making learning interactive and active, (3) language expert validation obtained 90% in the very appropriate category with the advantage that the language used is very easy to understand, (4) and expert student responses received 92.71% in the very appropriate category. Â Â